2022
DOI: 10.3390/toxins14120882
|View full text |Cite
|
Sign up to set email alerts
|

Potential Endocrine Disruption of Cyanobacterial Toxins, Microcystins and Cylindrospermopsin: A Review

Abstract: Microcystins (MCs) and cylindrospermopsin (CYN), although classified as hepatotoxins and cytotoxins, respectively, have been shown to also induce toxic effects in many other systems and organs. Among them, their potential endocrine disruption (ED) activity has been scarcely investigated. Considering the increasing relevance of ED on humans, mammals, and aquatic organisms, this work aimed to review the state-of-the-art regarding the toxic effects of MCs and CYN at this level. It has been evidenced that MCs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Thus, MC-LR can induce apoptosis and atrophy of gonadotropin-releasing hormone (GnRH) neurons in rats’ hypothalamus [ 284 , 285 ]. Although the molecular mechanism of MC-LR- induced apoptosis remains elusive, growing evidence supports that MCs and other cyanobacterial toxins, such as cylindrospermopsin, act as endocrine disruptors [ 286 , 287 ]. Recently, Shi and co-authors [ 288 ] demonstrated that acutely administrated MC-LR induces pathological changes in rat’s hypothalamus and pituitary gland and alters the transcription of genes involved in hormone biosynthesis.…”
Section: Mechanisms Of Brain Toxicitymentioning
confidence: 99%
“…Thus, MC-LR can induce apoptosis and atrophy of gonadotropin-releasing hormone (GnRH) neurons in rats’ hypothalamus [ 284 , 285 ]. Although the molecular mechanism of MC-LR- induced apoptosis remains elusive, growing evidence supports that MCs and other cyanobacterial toxins, such as cylindrospermopsin, act as endocrine disruptors [ 286 , 287 ]. Recently, Shi and co-authors [ 288 ] demonstrated that acutely administrated MC-LR induces pathological changes in rat’s hypothalamus and pituitary gland and alters the transcription of genes involved in hormone biosynthesis.…”
Section: Mechanisms Of Brain Toxicitymentioning
confidence: 99%
“…The pollution of environmental waters with aquatic toxins destroys marine and freshwater ecosystems, reduces the productivity of mariculture farms, damages tourism and recreational systems, and reduces biodiversity [ 2 ]. The consumption of contaminated fish and mollusks poses a great hazard to human health, causing intestinal disorders, and amnesic, hepatotoxic, and neuroparalytic symptoms, while chronic intake may provoke oncological diseases [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…With fossils dating back up to 3.6 billion years [3][4][5][6][7], these organisms are considered to have had a large influence on the evolution of our planet, such as through the generation of the oxygen atmosphere and the Great Oxidation Event [8][9][10][11]. More recently, cyanobacteria have also been shown to produce a large number of toxic compounds [12][13][14][15], including peptides, alkaloids and components of the cell wall, such as microcystins [16][17][18][19][20], cylindrospermopsins [21][22][23][24][25][26], anatoxin-a [27][28][29][30], anatoxin-a(S) (guanitoxin; [31][32][33][34][35][36][37]), saxitoxins [38][39][40][41][42], and LPS [43][44][45] as examples. With regard to human health, exposure to these toxins can occur through a wide range of exposure routes such as drinking water [46,47], the consumption of seafood in...…”
Section: Introductionmentioning
confidence: 99%